(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the complications of modified laparoscopic cholecystectomy and its association with umbilical port diameter. Study Design: Prospective study Place and Duration of Study: This study was conducted at the Department of Surgery, Central Park Teaching Hospital Lahore from 1stJuly 2018 to 30th June 2019. Materials and Methods: One hundred and fifteen patients of both genders with ages 20 to 60 years were included in this study. Patient’s detailed demographics were recorded after written consent. Patients with history of abdominal surgery were excluded. All the patients underwent modified laparoscopic cholecystectomy for gall bladder diseases. Post-operative pain was analyzed by VAS. Wound infection was recorded at 3rdpostoperative day and compared with size of umbilical incision. Results: There were 26 (22.61%) male patients and 89 (77.39%) patients were females. Most of the patients 45 (39.13%) were in the age group 31 to 40 years followed by 38 (33.04%) patients in the age group 41 to 50 years. 68 (59.13%) patients had umbilical port incision 5mm and 40.87% patients had 10mm. Mean pain score was 4.24±2.1 and 4.58±1.9 in patients with 5mm and 10mm port diameter with no significant difference. Wound infection was found in 6 (8.82%) and 5 (10.64%) in patients with 5mm and 10mm port diameter. At 12 weeks 6 (8.82%) and 15 (31.91%) patients with 5mm and 10mm port size diameter had developed port site hernia. Conclusion: Modified laparoscopic cholecystectomy is safe and effective treatment procedure with no major complications. No significant difference observed in term of pain score and wound infection according to port size diameter.